An Analysis of the Load Carrying Capacity and the State of Strain in Flat Elements of Arbitraty Thickness, with Circular Notches of Various Degrees of Sharpness, Subjected to Tension by an Impact Load - J. Miastkowski; H. Skrocki (Engineering Transactions, 1994)
The subject matter of the present analysis is the influence of the degree of notch sharpness on the limiting value of the thickness aboce which the energy of impact rupture of a structural element with a circular notch has a stable value.